Feedback as a Determinant of Online Assessment Validity: A Multidimensional Analysis in Indonesian EFL Higher Education - Mursalim; Alberth; Nggawu, La Ode; Ayu, Anugrah Puspita; Wahyudin Madil (Universitas Sulawesi Barat, 2026)
Although LMS-based online assessment is widely used, there is a paucity of empirical research studies that have investigated its multidimensional validity from students’ perspectives, especially in Indonesian higher education. The proposed cross-sectional survey research examines students’ perceptions of the validity and quality of online assessment in the English Education Department at Universitas Halu Oleo (UHO) delivered through the E-Green SPADA (Moodle-based) course platform. The study conceptualizes perceived validity based on multidimensional and argument-based validity frameworks that are prominent in contemporary research. A 25-item questionnaire (5-point Likert scale) that included construct validity, assessment fairness, feedback & support, learning impact, and affective impact was administered to a stratified random sample of 120 students during the final week of the semester. Exploratory factor analysis showed a five-factor structure (KMO = 0.89; Bartlett χ²(300) = 1650.3, p < .001), which explained 68.2% of the total variance, with acceptable internal consistency (α = .76–.89). The descriptive results showed that construct validity (M = 4.21, SD = 0.61) and assessment fairness (M = 4.08, SD = 0.65) were highly rated, while feedback & support received relatively low scores (M = 3.49, SD = .79). Feedback & support was the strongest predictor of overall perceived validity (β = .458, p < .001) in multiple regression analysis, and the full model accounted for 62.7% of the variance (R² = .627). These findings provide support for the consequential facet of validity in that the prompt, comprehensive, and accessible feedback can influence students’ confidence in online assessment. The research adds evidence from the Indonesian EFL higher education context and highlights the importance of LMS design features, instructor training, and feedback literacy programs that facilitate dialogic and responsive feedback practices.